Factors related to the death of diabetic patients with COVID-19 hospitalized in Joseph Raseta Befelatanana University Hospital in Antananarivo, Madagascar - Andrianiaina, Miora M. A.; Randrianomanana, Tsikinirina V.; Raherison, Rija E.; Razanamparany, Thierry; Raharinavalona, Sitraka A.; Rafamatanantsoa, Jean F.; Rakotomalala, Andrianirina D. P.; Andrianasolo, Radonirina L. (International Journal of Research in Medical Sciences, 2022)
Background: Diabetes mellitus is associated with severe and even fatal forms of COVID-19. The objective of this study was to identify the factors linked to the death of COVID-19 diabetic patients in order to improve their care. Methods: An analytical cross-sectional study was carried out in the endocrinology department of the Joseph Raseta Befelatanana University Hospital Center, Antananarivo, Madagascar. It has concerned all the cases of COVID-19 diabetics (162 patients) recorded from April 2020 to July 2021 (16 months). Results: In our study, the case fatality rate of COVID-19 in diabetics was 14.49%. Significant factors related to death, after univariate analysis, were: vascular complications including nephropathy (OR=4.74), neuropathy (OR=5.38) and ischemic heart disease (OR=3.9), presence of other comorbidities (OR=9.02), dyspnea (OR=4.60), seizures (OR=6.22) or alertness disorder (OR=4.35), lower oxygen saturation (p=0.04), pleurisy (OR=4.67), signs of cardiac decompensation (OR=3.46), an elevated mean blood sugar level (p<0.001), leukocytosis (p=0.02) and thrombocytopenia (p<0.001), impaired renal function (p=0.02) and pleurisy on chest imaging (OR=5.29). Conclusions: Death factors in diabetics with COVID-19 can be diverse. They do not only include the cardiovascular complications of the diabetes, but also a worse clinical respiratory presentation on the admission, a higher inflammatory syndrome, and a greater imbalance of blood sugar during the hospitalization.